Detection of some Bacteriocin Genes in Lactobacillus plantarum Isolated from some Food Products - Alebrahim, Alia Sabia; Alsaid, Walid; Alramo, Abir (Journal of natural sciences, life and applied sciences, 2022)
The study aims to detect of the genes (plnA, plnEF, plnA5p/S7) responsible for the production of bacteriocins in L. plantarum, after conducting an Antibacterial Activity test against Listeria monocytogenes. The Antibacterial Activity of isolates were in a cell- free extract using the Agar Well Diffusion Assay., then isolating the DNA of the isolates that gave Antibacterial Activity and checking their quality by electrophoresis technology. The PCR reaction was used to amplify the genes using specific primers to detection of three genes for bacteriocins (plnA, plnEF, plnA5p/S7) Where this research was conducted in the laboratories of microbiology and molecular genetics at the Faculty of Science, University of Aleppo, Aleppo, Syria. The results of the study showed that 3 isolates of (Lb35- Lb45- Lb55) showed Antibacterial Activity against Listeria monocytogenes with average inhibition halo diameter of 24 mm, 22 mm and 26 mm, respectively, and the electrophoresis results showed the presence of the three genes (plnA, plnEF, plnA5p/S7) in the isolates. The three are for L. plantarum with size bp516, bp579, bp450, respectively.